Application of Enterprise Architecture to Decentralized Architecture in Internet Databases - Novania Putri Amanda; Galuh Tresna Murti; Agung Nugroho; Stephen S.W. Situmorang (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
Enterprise architecture is a holistic, hierarchical and abstract description of the essential elements of an organization to maximize shareholder value over time. Enterprise Architecture (EA) is a way to structure enterprise information system elements which can be a set of models and relationships between enterprise elements used in planning, designing, and realizing an enterprise structure, business processes, information systems, and related infrastructure in inside. The database application architecture describes the basic design of the database application to be built. The database architecture describes the interaction diagram between the components that make up the database management system. These components include hardware devices, software, computer networks, and users. Distribution Architecture or Decentralized Architecture has its own advantages and disadvantages.